Sustained Release of Phosphates From Hydrogel Nanoparticles Suppresses Bacterial Collagenase and Biofilm Formation in vitro - Nichols, Dylan; Pimentel, Marja B.; Borges, Fernando T. P.; Hyoju, Sanjiv K.; Teymour, Fouad; Hong, Seok Hoon; Zaborina, Olga Y.; Alverdy, John C.; Papavasiliou, Georgia (Frontiers in Bioengineering and Biotechnology, 2019)
Intestinal disease or surgical intervention results in local changes in tissue and host-derived factors triggering bacterial virulence. A key phenotype involved in impaired tissue healing is increased bacterial collagenase expression which degrades intestinal collagen. Antibiotic administration is ineffective in addressing this issue as it inadvertently eliminates normal flora while allowing pathogenic bacteria to “bloom” and acquire antibiotic resistance. Compounds that could attenuate collagenase production while allowing commensal bacteria to proliferate normally would offer major advantages without the risk of the emergence of resistance. We have previously shown that intestinal phosphate depletion in the surgically stressed host is a major cue that triggers P. aeruginosa virulence which is suppressed under phosphate abundant conditions. Recent findings indicate that orally administered polyphosphate, hexametaphosphate, (PPi) suppresses collagenase, and biofilm production of P. aeruginosa and S. marcescens in animal models of intestinal injury but does not attenuate E. faecalis induced collagenolytic activity (Hyoju et al., 2017). Systemic administration of phosphates, however, is susceptible to rapid clearance. Given the diversity of collagenase producing bacteria and the variation of phosphate metabolism among microbial species, a combination therapy involving different phosphate compounds may be required to attenuate pathogenic phenotypes. To address these barriers, we present a drug delivery approach for sustained release of phosphates from poly(ethylene) glycol (PEG) hydrogel nanoparticles. The efficacy of monophosphate (Pi)- and PPi-loaded NPs (NP-Pi and NP-PPi, respectively) and a combination treatment (NP-Pi + NP-PPi) in mitigating collagenase and biofilm production of gram-positive and gram-negative pathogens expressing high collagenolytic activity was investigated. NP-PPi was found to significantly decrease collagenase and biofilm production of S. marcescens and P. aeruginosa. Treatment with either NP-Pi or NP-Pi + NP-PPi resulted in more prominent decreases in E. faecalis collagenase compared to NP-PPi alone. The combination treatment was also found to significantly reduce P. aeruginosa collagenase production. Finally, significant attenuation in biofilm dispersal was observed with NP-PPi or NP-Pi + NP-PPi treatment across all test pathogens. These findings suggest that sustained release of different forms of phosphate confers protection against gram-positive and gram-negative pathogens, thereby providing a promising treatment to attenuate expression of tissue-disruptive bacterial phenotypes without eradicating protective flora over the course of intestinal healing.